Pathogenicity of Aeromonas hydrophila in cultured African catfish (Clarias gariepinus) / Nora Faten Afifah Mohamad, Hassan Mohd Daid and Sharifah Raina Manaf - Mohamad, Nora Faten Afifah; Mohd Daud, Hassan; Manaf, Sharifah Raina (UiTM Press, 2022)
Aeromonas infections are becoming a serious risk issue in commercial aquaculture, and a wide range of fish and shellfish species has been documented as being vulnerable.Five isolates of Aeromonas hydrophila were identified from African catfish (Clarias gariepinus) cultured in Selangor, West Malaysia in this study. A conventional rapid identification approach (API 20E strip) was used for preliminary identification based on the biochemical properties of the isolated bacteria. Polymerase chain reaction (PCR) with the specific primer 16 rDNA, on the other hand, was used as an accurate and confirmed identification. A pathogenicity test via intramuscular (IM) injection was used to investigate the virulence of A. hydrophila. With a high degree of similarity (98%) to the NCBI or Genbank databases, the isolates were identified as A. hydrophila. The LD50 was calculated using pathogenicity test findings and was found to be 2.1  106.33 CFU mL−1, while 1  108 CFU mL−1in the experimentally injected fish, resulted in 100% mortality. Several organs, including the kidney, liver, and spleen,showed histopathological abnormalities. Those changes mainly include increase in the presence of hemosiderin deposits, congested portal vessels, vacuolated hepatocytes, generalised loss of tubular cells, and oedematous degeneration in the infected organs.